Oram eam in universum originis Poenorum. The Latinization of the Hispano-Phoenician coast (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
The aim of this work is the linguistic Latinization of the territories of southern Spain that in imperial times will make up the conventus Gaditanus (current province of Cádiz and the Andalusian Mediterranean coast). It is an area heavily influenced by the Phoenician cities and in which the Phoenician-Punic language survived until the beginning of the 1st century BCE. We will present the main elements of judgment that we have for the introduction of Latin and the disappearance of pheno-Punic, focusing on the epigraphy of production, the testimonies of everyday writing, and public epigraphy, including numismatics. Finally, we take into consideration what factors could influence the process of linguistic change.
Keywords: Andalusia; Punic Culture; Latinisation; Romanisation; Roman Spain